2009
DOI: 10.1007/s10142-009-0110-6
|View full text |Cite
|
Sign up to set email alerts
|

Matching the proteome to the genome: the microbody of penicillin-producing Penicillium chrysogenum cells

Abstract: In the filamentous fungus Penicillium chrysogenum, microbodies are essential for penicillin biosynthesis. To better understand the role of these organelles in antibiotics production, we determined the matrix enzyme contents of P. chrysogenum microbodies. Using a novel in silico approach, we first obtained a catalogue of 200 P. chrysogenum proteins with putative microbody targeting signals (PTSs). This included two orthologs of proteins involved in cephalosporin biosynthesis, which we demonstrate to be bona fid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 65 publications
7
92
0
1
Order By: Relevance
“…Protein Family-Previously, we identified a putative peroxisomal Lon protease (designated Pln) in the fungus P. chrysogenum by in silico identification of proteins that contain a putative peroxisomal targeting signal 1 (PTS1 (26). We confirmed the peroxisomal localization of this protein by fluorescence microscopy using cells producing a GFP-Pln fusion protein in conjunction with DsRed-SKL as a peroxisomal matrix marker (Fig.…”
Section: P Chrysogenum Peroxisomes Contain a Protease Of The Lon Amentioning
confidence: 76%
See 2 more Smart Citations
“…Protein Family-Previously, we identified a putative peroxisomal Lon protease (designated Pln) in the fungus P. chrysogenum by in silico identification of proteins that contain a putative peroxisomal targeting signal 1 (PTS1 (26). We confirmed the peroxisomal localization of this protein by fluorescence microscopy using cells producing a GFP-Pln fusion protein in conjunction with DsRed-SKL as a peroxisomal matrix marker (Fig.…”
Section: P Chrysogenum Peroxisomes Contain a Protease Of The Lon Amentioning
confidence: 76%
“…Biochemical Methods-Crude extract of P. chrysogenum cells were prepared as described previously (26). Protein concentrations were determined using the RC-DC assay system or BioRad assay kit (Bio-Rad) using bovine serum albumin (BSA) as a standard.…”
Section: Generation and Purification Of A Proteolytically Inactive Plnmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence alignment of yeast and fungal Aat2 proteins revealed that most contain either a PTS1 or PTS2 33, whereas Aat2p from Penicillium rubens displays both. However, H. polymorpha Aat2p does not possess a recognizable PTS, similar to Aat2p from several other yeast species (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several authors (131 -133) determined that the optimum pH for the in vitro conversion of IPN into PenN in A. chrysogenum cell-free extracts was 7.0, near the estimated pH of the peroxisomal lumen (107) . Additionally, the CefD1 and CefD2 homologous proteins have been identified in the peroxisome matrix of P. chrysogenum by mass spectrometry (134) .…”
Section: Role Of Two Peroxisomal Membrane Transporters In Cephalospormentioning
confidence: 99%